Difference analysis method of grid connection influence between CRE and DRE based on bus state trajectory - Xu, Chao; He, Sijing; Wang, Lu; Yu, Haifeng (Frontiers in Energy Research, 2023)
This paper presents a method to investigate the impact of centralized and distributed renewable energy on the power grid system, aiming to discern their differences. First, we derived the coupling relationship between renewable energy permeability and access point voltage under a simplified model. Second, we proposed a holomorphic embedding model designed for non-global variation, enabling the construction of the bus state trajectory index. This index is employed to analyze the influence of centralized and distributed renewable energy access on power grid stability and voltage under low-permeability conditions. Furthermore, under high permeability, we determined the limit permeability of centralized and distributed renewable energy. Last, we provided renewable energy configuration recommendations to enhance the system’s receptive capacity.